Extraction methods, composition and biological activity of polysaccharides from Arctium lappa L. – Short review (Research, Society and Development, 2021)
Since the end of the 20th century, the population exhibits health-related concerns, resulting in a trend towards the search for healthier foods with a focus on functional foods. Research has highlighted ingredients that when incorporated into the food make it functional, together with the benefits of this application in the characteristics of the final product. Polysaccharides are examples of functional ingredients that can collaborate with the texture of food products, as they demonstrate good emulsifying and thickening effects. Burdock polysaccharides (ALPS), a perennial plant that has a high medicinal value, have been evaluated in some studies for their potential as a beneficial ingredient for health, but few studies have evaluated their functionality for future applications as a thickener. Thus, this review aimed to present the different extraction methods, the composition of monosaccharides, the structural characteristics and biological activities of ALPS in order to provide information in a condensed way for future studies.